PENGARUH KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA MATERI JARINGAN DASAR DAN INTERNET KELAS VII SMP KRISTEN CITRA BANGSA KUPANG - Maria Yoaklina Letek; Jhon Enstein; Diana Yanni Ariswati Fallo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Maria Yoaklina Letek Latuan, 2025. The Influence of Learning Independence on Student Learning Outcomes in Informatics Subjects, Basic Network and Internet Material, Grade VII, Citra Bangsa Christian Middle School, Kupang. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University, Kupang. This study is entitled